2023
DOI: 10.3390/en16217258
|View full text |Cite
|
Sign up to set email alerts
|

Heat Production Capacity Simulation and Parameter Sensitivity Analysis in the Process of Thermal Reservoir Development

Yi Yang,
Guoqiang Fu,
Jingtao Zhao
et al.

Abstract: The development of a geothermal system involves changes in the temperature field (T), seepage field (H), stress field (M), and chemical field (C) and the influence among them and injecting the heat extraction working fluid into the injection well that flows (migrating) through natural fractures and exchanges heat with the geothermal high-temperature rock. At the same time, the injection of low-temperature working fluid will induce thermal stress, resulting in changes in the reservoir temperature field and stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Such a process is extremely complex due to the dynamics of spatiotemporal evolution, which involves changes in the temperature field, seepage field, and mechanical field. Yang et al [28] performed simulations of the heat production capacity of an underground reservoir, taking into account time-dependent mass conservation, heat conduction, and fluid heat transfer equations. The authors analysed the sensitivity of parameters related to the thermal performance and mining life of the deep thermal reservoir to thermal output.…”
Section: Review Of New Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a process is extremely complex due to the dynamics of spatiotemporal evolution, which involves changes in the temperature field, seepage field, and mechanical field. Yang et al [28] performed simulations of the heat production capacity of an underground reservoir, taking into account time-dependent mass conservation, heat conduction, and fluid heat transfer equations. The authors analysed the sensitivity of parameters related to the thermal performance and mining life of the deep thermal reservoir to thermal output.…”
Section: Review Of New Advancesmentioning
confidence: 99%
“…The results of the simulations showed that the injection temperature and the spacing of the well have little effect on the thermal efficiency and useful life of the mine, while the permeability, number, and length of the fracture have a significant influence. The authors emphasised the theoretical and practical importance of such studies [28].…”
Section: Review Of New Advancesmentioning
confidence: 99%
“…Nowadays, the world energy crisis and environmental problems are getting more and more serious, and hot dry rock (HDR) has become a new type of clean energy that countries around the world are focusing on researching and developing due to its extreme cleanliness, stability of operation, and wide spatial distribution [1][2][3]. Nevertheless, due to the low porosity and low permeability of HDR, the direct extraction of thermal energy is not an easy task, and it is usually necessary to form an enhanced geothermal system (EGS) through hydraulic fracturing techniques [4][5][6]. However, hot dry rock is generally deeply buried and has higher geostress anisotropy and stratum inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%